The effects of COVID-19 on labour market matching in Austria: A regional perspective - Michael Christl; Áron Kiss; Wolfgang Nagl (Austrian Institute of Economic Research (WIFO), 2025)
This paper examines labour market matching in Austria from 2008 to 2024, focusing on the regional impact of the COVID-19 pandemic. Using monthly administrative data, we estimate Beveridge curves and matching efficiency across federal states. Our results show that while COVID-19 temporarily disrupted labour market matching, mismatch unemployment returned to pre-pandemic levels relatively quickly. However, this national recovery masks persistent regional differences. Many industrial regions experienced structural declines in matching efficiency starting in 2014-2015. These findings highlight the need for regionally targeted labour market and training policies to address lasting disparities and support post-pandemic recovery.
Keywords: J21; J64; 330; Beveridge curve; unemployment; matching efficiency; COVID-19